Accuracy of Dengue Hemorrhagic Fever (DHF) Diagnosis Codes in Terms of Completeness and Accuracy of Medical Information - Heltiani, Nofri; Oktavia, Nova; Widyawati, Dwi (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
The completeness of the physical examination and the accuracy of laboratory results are crucial in supporting the accuracy of diagnostic codes. A preliminary survey of 10 Dengue Hemorrhagic Fever (DHF) medical records revealed that 4 (40%) were accurate and 6 (60%) were inaccurate. This was due to incomplete and inaccurate physical examination and laboratory results, which affected diagnosis and coding. This resulted in decreased data, information, and reporting quality, as well as the accuracy of INA-CBG rates, which could negatively impact the quality of hospital services. This study aimed to determine the accuracy of DHF diagnostic codes in terms of the completeness of medical information. This study used an observational, quantitative descriptive design, with 86 DHF medical records as the population and sample. The data used were secondary data obtained through observation using a checklist. The data were then processed and analyzed univariately using a frequency distribution. The results of this study are that from 86 DHF medical record files, 33 (38%) were found to have complete physical examinations, 12 (10%) were accurate laboratory test results, 8 (9%) were accurate diagnoses, and 8 (9%) were accurate diagnosis codes. It is expected that medical record officers, especially in the assembling section, will conduct medical record audits through qualitative analysis and improve coder skills through coding classification training.